1987
DOI: 10.1266/jjg.62.315
|View full text |Cite
|
Sign up to set email alerts
|

High order structure of Chironomus polytene chromosomes by scanning electron microscopy.

Abstract: Polytene chromosomes isolated from Chironomus salivary gland cells were processed with the Os04/TCH technique and examined by scanning electron microscopy (SEM) mainly using stereo techniques. When chromosomes were somewhat extended for preparation, band and interband regions became clearly visible. The bands appear to be dense masses of kinky fibers while the interband regions consist of the 30 nm chromatin fibers. On the other hand, in less extended chromosomes where band and interband regions were less dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…In contrast to the findings of Taniguchi and Takayama (1987), although those observations were done on Chironomus polytene chromosomes, 700-nm structures were found to exist in the chromosomes in the present study. The 700-nm-wide structures were generally present in all unstretched chromosomes investigated.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the findings of Taniguchi and Takayama (1987), although those observations were done on Chironomus polytene chromosomes, 700-nm structures were found to exist in the chromosomes in the present study. The 700-nm-wide structures were generally present in all unstretched chromosomes investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…Chromatin fibrils of 25 nm width were reported in whole mount EM studies of Drosophila polytene chromosomes (DuPraw and Rae, 1966). With the same method it was observed that in Chironomus polytene chromosomes bands appeared to consist of dense masses of kinky fibers while interbands consist of 30-nm fibers (Taniguchi and Takayama, 1987). In less extended chromosomes, coiled fibers of 200-nm width were observed both in bands and interbands.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation